KEBERMAKNAAN HIDUP PADA IBU RUMAH TANGGA YANG TERINFEKSI HIV-AIDS DI KOTA SURABAYA - Imroatu Sholikhati Setyo; Akhmad Fauzie; Dewi Mahastuti (Fakultas Psikologi Universitas Hang Tuah, 2018)
The purpose of this study is to understand how the process of achieving meaningful of life housewives living with HIV. The subjects in this study were two housewives PLHIV (People Living with HIV) who are already infected with HIV-AIDS for at least two years, with each one significant other. This study used a qualitative approach with descriptive case study, as well as in-depth interviews. Based on interviews and analysis of data, known when the subject was not received when it should be declared as a housewife living with HIV. Both subjects had to live life with a negative self-image on themself, because getting stigma and discrimination from society. The awareness to have a better life emerged after a meeting with other people living with HIV housewives as well as individual experts such as doctors or psychologists. The meaning of life back discovered two subjects because they have a belief in God. Of significance has been determined, the subjects begin to live life happily. Until the end of the two subjects get the results of the hard work that has been traversed. The changes do not significantly meaningful life is a process. In fact, every individual will follow the stages that exist precisely, considering each individual is a unique individual with characteristics that are owned respectively. This is what happened to the two housewives PLHIV in this study, that the process through which the meaningful of life does not follow a particular order.